Usable Live Programming - McDirmid, Sean (SPLASH Onward!, 2013)
Programming today involves code editing mixed with bouts of debugging to get feedback on code execution. For programming to be more fluid, editing and debugging should occur concurrently as live programming. This paper describes how live execution feedback can be woven into the editor by making places in program execution, not just code, navigable so that evaluation results can be probed directly within the code editor. A pane aside the editor also traces execution with entries that are similarly navigable, enabling quick problem diagnosis. Both probes and traces are refreshed continuously during editing, and are easily configured based on debugging needs. We demonstrate the usefulness of this live programming experience with a prototype.
To appear.